Determination of pharmacokinetic-pharmacodynamic cutoff values of oxytetracycline in calves and adult cattle using population pharmacokinetic modeling - Winter, Esther A.; Pelligand, Ludovic; Toutain, Pierre-Louis; Lees, Peter; Milanova, Aneliya; Gehring, Ronette (Frontiers in Microbiology, 2024)
IntroductionA harmonized clinical breakpoint for interpreting antimicrobial susceptibility testing of oxytetracycline in cattle is currently lacking in Europe. This study aimed to establish a pharmacokinetic/pharmacodynamic (PK/PD) cutoff to propose clinical breakpoints, facilitating reliable interpretation of antimicrobial susceptibility results in cattle.MethodsA meta-analysis of oxytetracycline pharmacokinetic data from 69 cattle was conducted, including 1,730 plasma concentration samples from animals administered 20 mg/kg intramuscularly and/or 20 or 40 mg/kg intravenously. A three-compartment model with two absorption phases was selected, incorporating age as a covariate for clearances and distribution volumes. The PK/PD cutoff was defined as the maximum MIC for which the fAUC/MIC index achieves the pharmacodynamic target in 90% of cattle given the standard dosing regimen. The pharmacodynamic index (PDI) target selected was established to 24 h, i.e., the average free plasma concentration of oxytetracycline over the 24-h dosing interval, under steady-state conditions, is equal to the selected MIC.ResultsSimulations indicated a PK/PD cutoff of 2 mg/L in adult cattle and 1 mg/L in calves for intramuscularly administered long-acting products at 20 mg/kg with a 48-hour efficacy duration. The difference is attributed to higher clearance rates in calves.DiscussionThe established PK/PD cutoffs, when used alongside the wild-type bacterial epidemiological cutoff, can aid in setting clinical breakpoints for oxytetracycline, supporting effective antimicrobial therapy in cattle and accounting for age-related pharmacokinetic differences.